2013
DOI: 10.1097/ajp.0b013e31826f9a71
|View full text |Cite
|
Sign up to set email alerts
|

Central Sensitization and Altered Central Pain Processing in Chronic Low Back Pain

Abstract: It tempting to speculate that ongoing nociception is associated with cortical and subcortical reorganization and may play an important role in the process of the chronification of LBP. Future prospective research should explore to what extent these changes are reversible and if this reversibility is associated with improved functioning of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
190
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(206 citation statements)
references
References 117 publications
(198 reference statements)
6
190
1
9
Order By: Relevance
“…Stress is considered a normal reaction to an unpleasant stimulus, such as LBP, but can, if sustained, cause illness and disease according to CATS. Sensitization of the central nervous system is further an increasingly recognized feature in many patients with CLBP (Roussel et al, 2013), in which an amplification of neural signaling elicits pain hypersensitivity (Woolf, 2011). Top-down approaches, such as CBT and exercise therapy, are implied for patients with central sensitization, and would as such be expected to decrease pain and disability.…”
Section: Discussionmentioning
confidence: 99%
“…Stress is considered a normal reaction to an unpleasant stimulus, such as LBP, but can, if sustained, cause illness and disease according to CATS. Sensitization of the central nervous system is further an increasingly recognized feature in many patients with CLBP (Roussel et al, 2013), in which an amplification of neural signaling elicits pain hypersensitivity (Woolf, 2011). Top-down approaches, such as CBT and exercise therapy, are implied for patients with central sensitization, and would as such be expected to decrease pain and disability.…”
Section: Discussionmentioning
confidence: 99%
“…11 The literature on CPM in chronic LBP is sparse. A recent review 12 found only 1 study, not supporting an alteration in CPM. 13 This confirms our assumption that measuring the time course may provide more information than single assessments.…”
Section: Cpm In Low Back Painmentioning
confidence: 93%
“…3 On the behavioral side, there is increasing evidence of sensorimotor malfunctions in patients with CLBP, related to chronic symptoms that might eventually result in disability. 4,5 Still, the underlying cortical processing of sensory information of the lower back has not been investigated in detail in (C)LBP patients. In healthy individuals, we have recently reported cortical processing of a nonpainful manual technique, that is, posterior-to-anterior (PA) pressure onto lumbar vertebrae.…”
mentioning
confidence: 99%